Combining Soft Systems Methodology, ethnographic observation, and discrete-event simulation: A case study in cancer care. Issue 10 (2nd October 2020) - Lamé, Guillaume; Jouini, Oualid; Stal-Le Cardinal, Julie
Abstract: We describe a project where discrete-event simulation (DES) is combined with Soft Systems Methodology (SSM) and ethnographic observation to support the improvement of patient flows in an outpatient chemotherapy unit and a chemotherapy preparation pharmacy unit. The project combines three interesting characteristics. First, we rely on ethnographic observation to explore the problem situation and frame the problem, a technique rarely reported in operational research (OR). Second, this leads us to define several root definitions, an aspect that remains overlooked in studies combining SSM and DES. Finally, the project stands at the interface between two departments (outpatient oncology unit and chemotherapy preparation pharmacy unit), a situation seldom explored in healthcare OR but where SSM has arguably a lot to offer to help identify and accommodate diverging objectives. We framed the problem, developed a simulation model, explored scenarios and refined a preferred one into a new business process. However, the proposed changes were not implemented. We analyse the outcomes of the project, the contribution of each method and their integration into an intervention. The paper provides insights on how SSM and DES can be combined in practice, and how the potential of ethnographic observation can be leveraged in this context.